2003
DOI: 10.1051/0004-6361:20030668
|View full text |Cite
|
Sign up to set email alerts
|

Solar prominence polarimetry

Abstract: Abstract. We measure the resonance polarization in solar prominences in Hα, Hβ and HeD 3 . A two-dimensional set-up with narrow-band filter, polarization analyzer and CCD camera is used to take prominence images in polarized light at high spatial resolution. Placed on a coudé telescope's hour axis, the observations near the equinoxia are free from purely instrumental polarization. Above the 0.1% noise limit, the Balmer lines do not show a polarization in contrast to the HeD 3 line. Here, we determine the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…Table 2 also shows the percentage contribution of the Hα radiation to the total brightness emission, given by %Hα = tB Hα /(tB Th + tB Hα ). Results are in good agreement for instance with Wiehr & Bianda (2003) and Leroy et al (1984), who measured the linear polarization of Hα radiation from prominences and found it varies within a few percent. Moreover, by the examination of a CME on August 31, 2007, Mierla et al (2011 obtained a Hα contribution to the total brightness emission more than 88% with a very low polarization, less than 5%.…”
Section: Estimate Of Hα Polarized Emission From the Blobssupporting
confidence: 82%
“…Table 2 also shows the percentage contribution of the Hα radiation to the total brightness emission, given by %Hα = tB Hα /(tB Th + tB Hα ). Results are in good agreement for instance with Wiehr & Bianda (2003) and Leroy et al (1984), who measured the linear polarization of Hα radiation from prominences and found it varies within a few percent. Moreover, by the examination of a CME on August 31, 2007, Mierla et al (2011 obtained a Hα contribution to the total brightness emission more than 88% with a very low polarization, less than 5%.…”
Section: Estimate Of Hα Polarized Emission From the Blobssupporting
confidence: 82%
“…(We recommend a reader of Léger and Paletou (2009) to change their Figure 9 for Figure 7.21 in Léger (2008).) This compatibility of the optical thinness with the ratio of lower than 8 settles down earlier indications of nonnegligible plasma optical thickness in He i D3 expressed in House and Smartt (1982); Athay et al (1983); López Ariste and Casini (2002); Casini et al (2003); and Wiehr and Bianda (2003) in the context of the observed ratios ranging from 6 to 7.6.…”
Section: Introductionsupporting
confidence: 85%
“…In a study of eight prominences, Athay et al (1983) found the He i D3 peak intensity ratios ranging from 6.1 to 7.6. Finally, López Ariste and Casini (2002) and Wiehr and Bianda (2003) reported peak intensity ratios of 6.8 and 6, respectively. While the former two studies employed the double-Gaussian model, the method of inferring the ratios in the latter two articles is unclear.…”
Section: Spectral Characteristics Of the Double-gaussian Modelmentioning
confidence: 97%
“…They found that the average magnetic field in prominences is consistent with earlier studies (see Leroy, 1989): a mostly horizontal field with a strength of about 20 G and with the magnetic vector pointing 20 • to 30 • off the prominence axis. In addition, the map shows magnetic fields significantly stronger than average (up to 80 G) in clearly organized patches within the prominence (also see Wiehr and Bianda, 2003;Casini, 2002, 2003;López Ariste and Aulanier, 2007). It is unclear whether these structures are related to the fine structures of quiescent prominences (e.g., vertical threads).…”
Section: Measurements Of Prominence Magnetic Fieldmentioning
confidence: 81%